Hubungan pola tidur dengan tingkat konsentrasi mahasiswa - Mushoffa, Ainun (Maliki Interdisciplinary Journal, 2026)
Sleep is a crucial physiological need for students as it plays a role in the body’s recovery process, maintains concentration, and supports academic achievement. This study examined the relationship between students’ sleep patterns and their concentration levels through a qualitative approach based on literature review. Data sources came from relevant scientific journals published between 2020 and 2025, then analyzed using content analysis and synthesis of findings. The results showed that sleep quality significantly impacts concentration, motivation, mental health, and academic performance. Students with adequate sleep are more productive and disciplined, while poor sleep patterns reduce memory and concentration, and increase the risk of stress. The main factors influencing sleep patterns include academic load, gadget use, daily routines, diet, and exercise. In conclusion, quality sleep is a key foundation for student academic success and health. Students are advised to maintain a consistent sleep schedule, limit gadget use before bed, and manage study time. Faculty should support this by providing academic load management and counseling services.